Empathy as a Mediator of the Effect of Dark Triad Personality, Social Support, and Demographic Factors on Cyberbullying Behavior in SMAN 10 Depok Students - Bernianti Lingga Sari; Yufi Andriani (‎‎‎TAZKIYA Journal of Psychology, 2022)
This study examines empathy as a mediator of the dark triad personality, social support, and demographic factors on cyberbullying behavior in SMAN 10 Depok students. The study was conducted on 428 students of SMAN 10 with purposive sampling technique. The measuring tools used in this study are Tudkuea's Cyberbullying Scale, The Short Dark Triad (SD3), The Interpersonal Reactivity Index (IRI), and the Multidimensional Scale of Perceived Social Support (MSPSS). Data analysis using Path Analyze with MPlus 7.4 software. Based on the results of the analysis of the research data, a fit model was found so that it can be concluded that the theoretical model of Empathy as a mediator of the influence of dark triad personality, social support & demographic factors on cyberbullying behavior fits with empirical data. This means that Empathy acts as a mediator of the influence of dark triad personality, social support & demographic factors on cyberbullying behavior. Then the results of research data analysis related to direct influence reported that there was a significant effect of Machiavellianism and gender directly on cyberbullying, while narcissism, psychopathy, family support, peers support, and significant others had no significant effect on cyberbullying. In addition, the results of the hypothesis test also reported that there was a direct significant effect of narcissism, peers support and gender on Empathy, while there was no significant effect of psychopathic machiavellianism, family support and significant other (teachers) directly on Empathy.